Temple occupation and the tempo of collapse at Angkor Wat, Cambodia - Carter, Alison K. (Proc Natl Acad Sci U S A, 2019)
The 9th–15th century Angkorian state was Southeast Asia’s greatest premodern empire and Angkor Wat in the World Heritage site of Angkor is one of its largest religious monuments. Here we use excavation and chronometric data from three field seasons at Angkor Wat to understand the decline and reorganization of the Angkorian Empire, which was a more protracted and complex process than historians imagined. Excavation data and Bayesian modeling on a corpus of 16 radiocarbon dates in particular demand a revised chronology for the Angkor Wat landscape. It was initially in use from the 11th century CE with subsequent habitation until the 13th century CE. Following this period, there is a gap in our dates, which we hypothesize signifies a change in the use of the occupation mounds during this period. However, Angkor Wat was never completely abandoned, as the dates suggest that the mounds were in use again in the late 14th–early 15th centuries until the 17th or 18th centuries CE. This break in dates points toward a reorganization of Angkor Wat’s enclosure space, but not during the historically recorded 15th century collapse. Our excavation data are consistent with multiple lines of evidence demonstrating the region’s continued ideological importance and residential use, even after the collapse and shift southward of the polity’s capital. We argue that fine-grained chronological analysis is critical to building local historical sequences and illustrate how such granularity adds nuance to how we interpret the tempo of organizational change before, during, and after the decline of Angkor.